Theophrastus of Eresus. - Fortenbaugh, William W.; Gutas, Dimitri.; Huby, Pamela M.; Sharples, R. W.; Theophrastus. (Philosophia Antiqua, 2011)
Interest in Theophrastus, Aristotle's pupil and successor as head of the Peripatetic School, has increased considerably since the 1992 publication of Theophastus of Eresus: Sources for his Life, Works, Thought and Life . Now comes an extensive commentary on the ethical sources. It considers Theophrastus in relation to Aristotle, to other members of the Peripatos and to the Stoic philosophers who became Theophrastus' rivals. Special attention is given to Theophrastus' insistence that virtue by itself cannot guarantee happiness. Also to the difference between manners and moral virtue, the relation between innate character and fate, the value of marriage and how animal behavior relates to that of human beings.